Alternation through Death: Is Gerontocracy an Equilibrium?. (December 2018) - Magni Berton, Raul; Panel, Sophie
According to minimalist theories of democracy, the reason why civil conflicts are less frequent in democracies is that opposition parties can reasonably expect to win the next elections: they then prefer to wait than to rebel. In dictatorships, waiting until the dictator dies is generally much costlier. This waiting time, however, is considerably shortened when the dictator is old. Therefore, the risk of domestic conflict should decrease along with the age of autocratic leaders. Based on 160 countries from 1960 to 2008, our empirical analysis shows that the leader's age decreases the likelihood of violent rebellion in dictatorships, but not in democratic regimes.